After Anna - Scottoline, Lisa (St. Martin's Press, 2018)
"Nobody cuts deeper than family... Noah Alderman, a doctor and a widower, has remarried a wonderful woman, Maggie, and for the first time in a long time he and his son are happy. But their lives are turned upside down when Maggie's daughter Anna moves in with them. Anna is a gorgeous seventeen-year-old who balks at living under their rules though Maggie, ecstatic to have her daughter back, ignores the red flags that hint at the trouble that is brewing. Events take a deadly turn when Anna is murdered and Noah is accused of the crime. Maggie must face not only the devastation of losing her only daughter, but the realization that her daughter's murder was at the hands of a husband she loves. New information sends Maggie searching for the truth, leading her to discover something darker than she could have ever imagined" --